2018
DOI: 10.1155/2018/5364628
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic Monitoring of Energy Changes in Deep Tunnels during the TBM Tunneling of the Jinping II Hydropower Station

Abstract: e TBM tunneling at the Jinping II hydropower station in Southwest China has received extensive concerns around the world because of its large engineering scale and the high rockburst risks faced in the tunnel advancement. e associated energy changes of rockbursts and control method for safe TBM tunneling are to be further investigated. A movable microseismic (MS) monitoring system was established to capture the MS events and rockbursts when the TBM excavated the headrace tunnel #1 at the Jinping II hydropower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…e potential risk of excavation of highly stressed, hard, brittle rock mass is the energy release and the rock damage in the forms of spalling and strain burst. It was reported that severe strain burst occurred along a considerable length of tunnel section, and energy changes were monitored during tunnel excavation of the China Jinping II hydropower station project [37,38]. It is thus important to develop a technique to monitor the damage development process and amount of released energy for the identification of damage occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…e potential risk of excavation of highly stressed, hard, brittle rock mass is the energy release and the rock damage in the forms of spalling and strain burst. It was reported that severe strain burst occurred along a considerable length of tunnel section, and energy changes were monitored during tunnel excavation of the China Jinping II hydropower station project [37,38]. It is thus important to develop a technique to monitor the damage development process and amount of released energy for the identification of damage occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…e microseisms determine the failure characteristics and mechanism of rockburst [19][20][21][22][23][24]. To date, the interactive mechanism between microseismic activity and supporting structure remains less investigated, and the microseismic activity is rarely used to guide support strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al studied the rockburst phenomenon using the numerical simulation method and developed a new local energy release rate (LERR) index, which can satisfactorily predict the depth of the outburst pit and the intensity of the rockburst, providing a new method to evaluate the rockburst orientation in deep underground projects [14]. Zhuang et al conducted realtime monitoring of microvibration events and rockburst during the TBM excavation of Jinping II diversion tunnel 1 # and found that the top guide tunnel excavation method can effectively reduce the risk of rockburst during TBM tunnel excavation [15]. It was found that the unloading rate has an important influence on the degree and failure models of rockburst during the excavation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%